2018
DOI: 10.17706/ijeeee.2018.8.1.58-65
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Patient Loyalty by Investigating Its Relationship with Relationship Quality, Alternative Attractiveness, and Patient Gratitude in Hospitals

Abstract: Abstract:Recently hospitals are facing several challenges in a competitive medical market, how to enhance physician-patient relationship becomes an important concern for hospitals to better improve medical quality and patient loyalty. However, the enhancement of patient loyalty through a better physician-patient relationship is still ambiguous in healthcare field. The purpose of this study aims to examine the physician-patient interaction, and to further investigate the relationships among relationship quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…First, it is among the first studies to focus on patient gratitude and differentiate it from patient satisfaction in the context of online healthcare. While patient gratitude towards medical professionals is widely studied in offline healthcare, it has received limited attention in the online healthcare context (Hsieh et al, 2018; Huang et al, 2019). Prior studies have mainly treated patient gratitude as an indicator of patient satisfaction, failing to recognise the difference between satisfaction and gratitude (Yang et al, 2019; Zhang, Wu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is among the first studies to focus on patient gratitude and differentiate it from patient satisfaction in the context of online healthcare. While patient gratitude towards medical professionals is widely studied in offline healthcare, it has received limited attention in the online healthcare context (Hsieh et al, 2018; Huang et al, 2019). Prior studies have mainly treated patient gratitude as an indicator of patient satisfaction, failing to recognise the difference between satisfaction and gratitude (Yang et al, 2019; Zhang, Wu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Second, another important outcome of patient evaluation in online healthcare, namely gratitude, has been largely overlooked in the existing literature. In offline physician–patient interactions, patients often express gratitude towards medical staff for their efforts in preserving their health and well‐being, and such expressions of gratitude are known to contribute to establishing patient loyalty and long‐term physician–patient relationships (Hsieh et al, 2018; Huang et al, 2019). However, previous studies have mainly considered patient gratitude in the context of online healthcare as an indicator of patient satisfaction, while neglecting its distinctive role.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…9,15 Namun pada hasil penelitian lainnya ditemukan juga bahwa loyalitas konsumen tidak dipengaruhi oleh nilai konsumen, 16,17 ataupun kepercayaan konsumen. 9,18 Oleh karena belum ditemukan konsensus mengenai hasil penelitian diatas maka penelitian ini bertujuan untuk menginvestigasi pengaruh nilai dan kepercayaan konsumen terhadap loyalitas konsumen, kepercayaan konsumen terhadap nilai konsumen, serta tiga dimensi kualitas pelayanan terhadap kepercayaan konsumen.…”
Section: Manajemen Kesehatan Manajemen Kesehatan Indonesiaunclassified
“…Physicians who communicate friendly with their patients present fewer disputes and thus suffer less disruption in the process of medical treatment. 33 Likewise, further studies may consider level of patient gratitude to identify the impact of moderation effect on the physician-patient relationship.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Few studies have clearly identified the connection between patient gratitude and physician-patient relationship, particularly the effect of patient gratitude on patient loyalty. 32,33 As health care organizations seek to create a long-term relationship with the patient, understanding how patient gratitude impacts physician-patient relationship is essential. It is therefore important to recognize the role of the patient’s gratitude on a long-term physician-patient relationship.…”
Section: Introductionmentioning
confidence: 99%